Right ventricular longitudinal contractility mismatch: a novel diagnostic marker of right ventricular arrhythmogenic cardiomyopathy. (3rd October 2022) - Bocchino, P P; Frea, S; Angelini, F; Gravinese, C; Gallone, G; Clivio, A; Toso, E; Giustetto, C; De Ferrari, G M
Abstract: Background: The structural alterations of arrhythmogenic right ventricular (RV) cardiomyopathy (ARVC) mainly involve the RV outflow tract (RVOT), but RVOT systolic function has been poorly investigated. Purpose: We aimed to evaluate the Doppler Velocity Ratio (DVR) as a novel echocardiographic parameter for ARVC diagnosis. Methods: 30 consecutive ARVC adult patients, 45 asymptomatic healthy volunteers and 45 consecutive patients with RV dysfunction due to ARVC mimics were prospectively enrolled between May 2019 and December 2021 and received complete transthoracic echocardiography examinations. The DVR was calculated as the ratio of RV free wall systolic velocity to RVOT systolic velocity at Doppler tissue imaging. The main study outcomes were to compare the DVR among ARVC patients, healthy controls, and mimics and to assess its diagnostic value in ARVC. Results: 120 patients were included. Mean age was 55±17 years; 46 (38.3%) patients were female. The DVR was significantly higher in ARVC subjects (1.59±0.41) compared to both healthy controls (1.16±0.14, P<0.001) and mimics (1.17±0.23, P<0.001), but similar between healthy controls and mimics (P=1.000). The DVR cut-off value with the highest accuracy for ARVC diagnosis was 1.33 (sensitivity=80.0%, specificity=86.7%). The area under the curve of DVR alone was significantly superior to that of the major echocardiographic 2010 Task Force Criteria (0.833 vs 0.672 respectively, P=0.034). The net reclassification improvement for DVR alone against the major echocardiographic 2010 Task Force Criteria was 32.2% (P=0.023). Conclusions: The DVR is a simple novel echocardiographic parameter with high accuracy for ARVC diagnosis. Funding Acknowledgement: Type of funding sources: None.